The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s11832-015-0660-1
|View full text |Cite
|
Sign up to set email alerts
|

A radiographic study of the distal femoral epiphysis

Abstract: Purpose Previous studies have described the complex undulation pattern in the distal femoral physis. We investigated whether standard radiographs can visualize these landmarks, in order to guide hardware placement in the distal immature femur.Methods We studied 36 cadaveric immature femora in specimens 3 to 18 years of age. Anteroposterior (AP) and lateral radiographs were obtained with and without flexible radiodense markers placed on the major undulations and were analyzed to determine the relative height or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…12 Previous investigations into its topographical anatomy have revealed a distinctive pattern that changes with increasing age. 8,9 A study by Ngyuen et al 8 involving 36 cadaveric femora in children aged between three and 18 years found that, with increasing age, there was a decrease in the radiographic height of the central peak’s position relative to a line connecting the medial and lateral aspects of the physis (R 2 = 0.75), identical to the physeal line used in this study. They noted that identifying the central peak on lateral radiographs was more difficult with correlations for the central peak being less consistent (ICC = 0.62).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…12 Previous investigations into its topographical anatomy have revealed a distinctive pattern that changes with increasing age. 8,9 A study by Ngyuen et al 8 involving 36 cadaveric femora in children aged between three and 18 years found that, with increasing age, there was a decrease in the radiographic height of the central peak’s position relative to a line connecting the medial and lateral aspects of the physis (R 2 = 0.75), identical to the physeal line used in this study. They noted that identifying the central peak on lateral radiographs was more difficult with correlations for the central peak being less consistent (ICC = 0.62).…”
Section: Discussionsupporting
confidence: 62%
“…During skeletal maturation, the topographical anatomy of the distal femoral physis has three major undulations, central peak, lateral ridge, and medial peak, that change with increasing age. 8,9 Importantly, the central ridge decreases linearly in height relative to a line connecting the medial and lateral aspects of the physis. 9 This anatomical parameter represents a potential landmark, easily identified on routine radiographs of the knee, that could be used to estimate skeletal maturity.…”
mentioning
confidence: 99%
“…The location of the MPFL femoral attachment site relative to the femoral growth plate is of critical importance to better inform clinicians on the optimal location for femoral attachment reconstruction. Despite the presentation of all available information regarding the MPFL femoral attachment site in young (\18 years) participants in this review, our study has not been able to provide additional scientific evidence on the best practice for tunnel positioning in surgical reconstruction (proximal or distal to the growth plate) for young participants beyond that presented by Nguyen et al 58,59 As a result, future studies should present clear information regarding the MPFL attachments relative to the growth plates, together with participant age. In addition, follow-up studies to assess the efficacy of reconstruction for restoring patellar function should be presented.…”
Section: Limitationsmentioning
confidence: 84%
“…71 In such cases, the close proximity of the growth plate to the femoral attachment of the MPFL presents a critical challenge because damage to the physis during reconstruction can potentially impair femoral skeletal growth. 44,84 As a result, Nguyen et al 58,59 recommended taking both anteroposterior and lateral radiographs into consideration to ensure a more precise and secure definition of the femoral physis but also that tunnels are drilled at an angle of 15° to 20° distally and anteriorly to minimize the risk of physis damage. Surgically, however, it is difficult to ensure a safe drilling trajectory intraoperatively unless using fluoroscopy to check both the starting point and the path of the guide wire.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation